Impact of Internal Control on Varietal and Sowing Qualities of Seeds - Yakubov Muzaffar; Rashidova Dilbar; Oripov Sherali (BIO Web of Conferences, 2023)
The manifestation of main attributes which form the yield and oil-bearing capacity depends strongly on cultivation conditions and such attributes as height of plants, height of first inflorescence and 1000 kernels weight are characterized by high heritability. The research was conducted in Gallyaaral Experimental Station, farms of Jizzak oblast. Wheat varieties “Semrug”, “Dustlik”, “Durdona” sown under irrigated conditions and “Istiklol” sown under rainfed conditions were used for research. Biometric observations of plant growth and development were carried out on the crops during the growing season. It was determined that the varietal purity corresponds to the requirements of the standard, and the sown seeds can be used for further reproduction. The correlation analysis revealed a positive relationship with yield. A weak correlation was shown for Safflower varieties between yield and number of seeds in the boll (r=0.18) for oilseed flax (r=0.18). The oil content varied from 20% to 26.5 and exceeded the standard.